2018
DOI: 10.31024/ajpp.2018.4.6.17
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of Betulinic acid on ageing and scopolamine-induced learning and memory impairment in rats

Abstract: Background: Ageing is a natural process which includes a progressive decline in cognitive functions as a result of maladaptation of cholinergic neuronal activity. The reason behind ageing-induced cholinergic neuronal loss is largely unknown, however, oxidative stress is speculated to be majorly involved in its aetiology. In the present Objectives: study, the effect of betulinic acid was evaluated on learning and memory in aged rats as well as scopolamine-induced amnesic rats. Betulinic acid (25 and 50 mg/kg; p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 64 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…It has been demonstrated that betulinic acid also improves learning and memory of aged as well as scopolamine-induced amnesic rats. Furthermore, betulinic acid also decreased lipid peroxidation and nitrite level, and increased the levels of reduced glutathione and superoxide dismutase [40]. Ursolic acid isolated from Micromeria cilicica has been shown to inhibit AChE and BChE at IC 50 of 93.80 and 41.10 µM, respectively [41].…”
Section: Potential Anticholinesterase Activity Of Identified Triterpementioning
confidence: 97%
See 3 more Smart Citations
“…It has been demonstrated that betulinic acid also improves learning and memory of aged as well as scopolamine-induced amnesic rats. Furthermore, betulinic acid also decreased lipid peroxidation and nitrite level, and increased the levels of reduced glutathione and superoxide dismutase [40]. Ursolic acid isolated from Micromeria cilicica has been shown to inhibit AChE and BChE at IC 50 of 93.80 and 41.10 µM, respectively [41].…”
Section: Potential Anticholinesterase Activity Of Identified Triterpementioning
confidence: 97%
“…Terpenoids are reported as potential leads for the development of cholinesterase inhibitors [39][40][41]. For this reason, in vitro cholinesterase inhibition assays were also performed on the commercially available triterpenes betulinic, corosolic, maslinic, oleanolic and ursolic acids that were found in M. diffusa, in order to compare the activities of sample fractions containing these triterpenes.…”
Section: Identification and Quantification Of Phytochemicals By Liquimentioning
confidence: 99%
See 2 more Smart Citations